Mathematics teachers’ mathematical beliefs: A comprehensive review of international research - Žalská, Jana (Scientia in educatione, 2013)
This review of literature provides a comprehensive introduction to the research on the mathematical beliefs of mathematics teachers. It both describes the theoretical framework and provides practical illustrations of studies and relevant phenomena. Special attention is given to the relationship between mathematical beliefs and teacher professional development, to critical methodological issues particular to the research, and to teacher belief typological studies. Relevant research in the Czech Republic is outlined and situated within the international body of literature. Further perspectives and interests of investigation, as related to the mathematical beliefs of teachers, are suggested.